2019
DOI: 10.1177/0954406219884979
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on the combustion characteristics in a porous-free flame burner for lean mixtures

Abstract: The present work implements a numerical simulation to investigate the combustion process in a porous-free flame burner. The non-equilibrium thermal condition is performed, and discretization and solving of the governing equations are conducted in a two-dimensional axisymmetric model. In order to simulate the combustion process, a reduced chemical kinetic mechanism of GRI 3.0, which includes 16 species and 41 reactions, is used. In order to prove the precision of the numerical method, some experimental tests ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…A conclusion that can be drawn from Figure 3b,c is that the smaller the pore size and interval, the lowe the heat transfer. The same conclusion is also reached in GS's experiments [17]. As shown in Figure 3a, the shape of the HRR curve varies substantially with the pore shape-the different pore shapes have different combustion performances, as expected.…”
Section: Combustion Performancesupporting
confidence: 83%
See 1 more Smart Citation
“…A conclusion that can be drawn from Figure 3b,c is that the smaller the pore size and interval, the lowe the heat transfer. The same conclusion is also reached in GS's experiments [17]. As shown in Figure 3a, the shape of the HRR curve varies substantially with the pore shape-the different pore shapes have different combustion performances, as expected.…”
Section: Combustion Performancesupporting
confidence: 83%
“…A conclusion that can be drawn from Figure 3b,c is that the smaller the pore size and interval, the lower the heat transfer. The same conclusion is also reached in GS's experiments [17].…”
Section: Smoke Production Rate and Temperaturesupporting
confidence: 82%
“…In addition, as the swirl number of the third premixed stage increases from 0.6 to 1.2, the emissions of NO and CO decrease by 28.7% and 75%, respectively. Ghorashi et al, 12 investigated the combustion process implements by a numerical simulation in a porous-free flame burner. They found by decreasing the pore density of porous medium, the flame stability is extended.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[17][18][19] Several studies on the PMC indicated the advantages of using this technology in enhancing combustion performance, reducing the pollutant emission and working at high power densities. [20][21][22][23] Pollutant emissions and combustion performance of premixed ammoniahydrogen-air flame through a porous media block were evaluated experimentally by Nozari et al 24 They examined the burner efficiency and NO x emission at high ammonia concentrations over a wide range of equivalence ratios. Results indicated that the minimum NO x emission was measured at rich fuel conditions.…”
Section: Introductionmentioning
confidence: 99%